Shelf life of frozen desalted cod (Gadus morhua) - Dargentolle, Cecile; Sveinsdóttir, Hildur Inga; Baldursson, Jónas; Arason, Sigurjón; Sveinsdóttir, Kolbrún (Zenodo, 2024)
A part of the project „Saltfiskur til framtíðar“ was to study the quality and shelf life of desalted cod in frozen storage. The focus of the experiment described in this report was on desalting of loins and tail parts of fully salt cured cod fillets, followed by three different types of treatment before frozen storage. The first group was frozen and then glazed, packed in plastic and carboard boxes, the second group was frozen and then glazed and vacuum packed, and the third group was treated with citric acid (0.2 %), then frozen, glazed and vacuum packed. Before the treatments, samples were split into either loin or tail samples within each group. The quality and shelf life of the three groups, both loins and tails were evaluated at the beginning of storage and after 6, 9, 12 and 27 months of frozen storage at -25°C, by sensory evaluation, microbiological and chemical analysis. The three treatments did not significantly affect the shelf life of the frozen desalted cod samples, and even after 27 months of frozen storage all samples were considered of acceptable quality related to their chemical composition, microbiological content and sensory attributes. _____ Hluti verkefnisins „Saltfiskur til framtíðar“ snéri að því að meta gæði og geymsluþol fyrir frystan útvatnaðan saltfisk. Áhersla tilraunarinnar sem lýst er í þessari skýrslu var á útvötnun hnakkastykkja og sporðstykkja fullverkaðra saltfiskflaka, sem voru svo meðhöndluð á þrenna vegu fyrir frystigeymslu. Einn hópur var frystur og íshúðaður og pakkað í plast, annar hópur var frystur, þá íshúðaður og vakúm pakkaður og þriðji hópurinn var meðhöndlaður með sítrónusýru (0.2%), þá frystur, íshúðaður og vakúm pakkaður. Fyrir hverja meðhöndlun var sýnum skipt í annað hvort hnakkastykki eða sporðstykki. Gæði og geymsluþol hópanna þriggja, bæði hnakkastykkja og sporðstykkja, var metið við upphaf geymslu og eftir 6, 9, 12 og 27 mánaða frystigeymslu við -25°C, með skynmati, efna- og örverumælingum. Óverulegur munur reyndist vera á hópunum þremur varðandi geymsluþol, ...